A new ABCG2 null allele with a 27‐kb deletion including the promoter region causing the Jr(a−) phenotype. Issue 6 (18th December 2014) - Ogasawara, Kenichi; Osabe, Takahiro; Suzuki, Yumi; Tsuneyama, Hatsue; Isa, Kazumi; Kawai, Miho; Obara, Kumi; Ogiyama, Yoshiko; Ito, Shoichi; Uchikawa, Makoto; Satake, Masahiro; Tadokoro, Kenji
Abstract : Background: The high‐prevalence antigen Jr a is carried on the ATP‐binding cassette transporter ABCG2. The ABCG2 gene consists of 16 exons and its translation start codon is located on the second exon. Although the occurrence of the Jr(a−) phenotype is rare, several ABCG2 null alleles have been reported. We report a new ABCG2 null allele having a large deletion in this study. Study Design and Methods: The Jr a status was determined by standard serologic tests and genomic DNA was isolated from whole blood. Exons 1 to 16 and the 5′‐untranslated region of the ABCG2 gene were analyzed by polymerase chain reaction and sequencing. Expression of the ABCG2 protein on red blood cells was examined by immunoblotting. Results: A Jr(a−) blood donor had a novel allele having a 27‐kb deletion including noncoding Exon 1 and the promoter region of ABCG2, and the donor was apparently homozygous for the allele. In addition, we found three more individuals having heterozygosity for the same allele, with ABCG2*01N.01 having c.376C>T (p.Q126X), but did not find the allele having the 27‐kb deletion in 3000 Jr(a+) individuals. Immunoblotting revealed that the ABCG2 protein was not found to be expressed in the individual with homozygosity for the ABCG2 27‐kb deleted and in two individuals with an ABCG2 27‐kb deleted/ABCG2*01N.01 genotype, which indirectly allows to conclude that the 27‐kb deletion is responsible for a null ABCG2 allele. Conclusion: We first identified an ABCG2 null allele (provisional ISBT allele number ABCG2*01N.23 ) having a large deletion including the promoter region.